Bacillus subtilis spores as an adjuvant to enhance the protection efficacy of the SVCV subunit vaccine (SVCV‐M protein) in German mirror carp (Cyprirnus Carpio Songpa Linnaeus Mirror). (5th May 2021) - Liu, Jia; Cheng, Yi; Lu, Yuting; Xia, Changge; Wang, Nan; Li, Yuehong
Abstract: The present study evaluated the adjuvant effects of Bacillus subtilis ( B . subtilis ) spores on the immune response induced by an SVCV‐M protein, which was equivalent to a subunit vaccine in German mirror carp ( Cyprirnus Carpio Songpa Linnaeus Mirror ). The following results were observed: in vitro, there were no toxic effects of B . subtilis spores and SVCV‐M protein on the viability of epithelioma papulosum cyprini (EPC) cells. In addition, B . subtilis spores can significantly reduce the oxidative damage of the spring viraemia of carp virus (SVCV) on EPC cells, but protein‐M had no significant effects on the oxidative damage of EPC cells. In vivo, higher levels of specific IgM could be detected in the protein‐M+ B . subtilis spores group, compared with that in PBS, B . subtilis spores and Protein‐M groups. Immune‐related indexes including the activities of LZM and AKP and the content of C3 and C4 in the protein‐M+ B . subtilis spores group were strongly upregulated. Immune‐related genes had the same trend as the immune‐related indexes. Furthermore, the antioxidant capacity of the protein‐M+ B . subtilis spores group was also better than that of PBS, B . subtilis spores and Protein‐M groups. Finally, the highest survival rate (59.69%) was observed in the protein‐M+ B . subtilis spores group, while the survival rate was 8.89% in protein‐M group, and 0% in the PBS and B . subtilis spores groups. This study suggests B . subtilis spores as an adjuvant that can enhance the protection efficacy of the SVCV subunit vaccine (SVCV‐M protein) in common carp.